2008
DOI: 10.1242/jcs.028605
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial nucleoids undergo remodeling in response to metabolic cues

Abstract: Mitochondrial DNA is organized as a nucleoprotein complex called the nucleoid. Its major protein components have been identified in different organisms, but it is yet unknown whether nucleoids undergo any form of remodeling. Using an in organello ChIP-on-chip assay, we demonstrate that the DNA-bending protein Abf2 binds to most of the mitochondrial genome with a preference for GC-rich gene sequences. Thus, Abf2 is a bona fide mitochondrial DNA-packaging protein in vivo. Nucleoids form a more open structure und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 37 publications
3
82
0
1
Order By: Relevance
“…Previous mechanistic studies using purified recombinant mitochondrial transcription components led to the conclusion that the core human transcription machinery is an obligate threecomponent system comprising POLRMT, have been shown to change their composition as a way to adjust mtDNA expression in response to metabolic signals. 24 That mammalian nucleoids are also not packaged by mtTFA alone is consistent with this concept and has been proposed by others to dictate their relative activity with regard to transcription and replication. 22,[25][26][27] Other predictions of the h-mtTFAregulated two-component model are that significant transcription should persist when mtTFA levels are low or absent and that altering the mtTFA:mtDNA ratio should affect transcriptional output.…”
Section: Human Mitochondrial Transcription Initiation: Lessons From Psupporting
confidence: 76%
“…Previous mechanistic studies using purified recombinant mitochondrial transcription components led to the conclusion that the core human transcription machinery is an obligate threecomponent system comprising POLRMT, have been shown to change their composition as a way to adjust mtDNA expression in response to metabolic signals. 24 That mammalian nucleoids are also not packaged by mtTFA alone is consistent with this concept and has been proposed by others to dictate their relative activity with regard to transcription and replication. 22,[25][26][27] Other predictions of the h-mtTFAregulated two-component model are that significant transcription should persist when mtTFA levels are low or absent and that altering the mtTFA:mtDNA ratio should affect transcriptional output.…”
Section: Human Mitochondrial Transcription Initiation: Lessons From Psupporting
confidence: 76%
“…In vivo, Abf2p is essential for stabilization of mtDNA in cells grown on a fermentable carbon source such as glucose (Diffley & Stillman, 1991). In addition, it has been shown that Abf2p influences the level of yeast mtDNA recombination intermediates (MacAlpine et al, 1998) and is involved in remodelling of mt-nucleoids in response to changes in mitochondrial metabolism (Kucej et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These structures are dynamic macrocomplexes located in the mitochondrial matrix, and they act as units of mtDNA replication and inheritance with composition that can undergo remodeling in response to metabolic stresses (7,23,47). Using bromodeoxyuridine (BrdU) incorporation, nucleoids have been shown to be the sites of mtDNA replication in yeast and mammalian cells (35,39).…”
mentioning
confidence: 99%